PROCESS OF EXPLORING CRITERIA FOR OBSERVING CHILDHOOD PLAY TO SUPPORT EARLY CHILDHOOD TEACHERS - Yoo, YungEui; Cho, BoKyoung; Yang, SunHee; Lee, MyeongHa (PEOPLE: International Journal of Social Sciences, 2024)
The purpose of this study is to investigate the process of exploring criteria for observing childhood play to support early childhood teachers. This study was conducted using a convergent design among mixed methods. ‘Literature research’ and ‘Delphi survey technique’ were used as methods of quantitative data collection, and ‘participation observation’ was used as a method of qualitative data collection. As a result of the study, observation criteria for a total of 21 questions in 3 areas were derived, including 7 questions on ‘play flow’, 7 questions on ‘play motivation’, and 7 questions on ‘peer play behavior’. This criteria for observing childhood play helps early childhood teachers to understand childhood play in depth from the children’s perspective. In addition, it is expected that this standard can be used as a standard for observing childhood play with increased objectivity by reducing cases where each early childhood teacher who uses this standard interprets it differently due to subjective opinions. Furthermore, It is expected that this criterion will help early childhood teachers in kindergartens accurately understand childhood play and support childhood play.